THE TRANSLATION STRATEGIES OF CULTURAL WORDS IN AHMAD TOHARI'S DANCER - Nitisari, Dwi (UG Journal, 2016)
The aim ofthis research is to find out the translation strategies by examining twonovels, which are "Ronggeng Dukuh Paruk" by Ahmad Tohari and the Englishtranslation version "Dancer" by Rene T.A. Lysloff. The writer uses a descriptivequalitative as the research method because the result ofthe analysis are concernedwith providing descriptions of phenomena that occur naturally, without theintervention ofan experiment. After classifying the data based on its strategies,this research shows that there are eight strategies which are used by the translatorto translate the cultural words. From eighty seven data (sentences that containingthe cultural words) which are identified, there are 15 cultural words (17,24%) byusing general words, 17 cultural words (19,54%) by using cultural substitution,18 cultural words (20,69%) by loan word or loan wordplus explanation, 27 culturalwords (31,03%) by descriptive equivalent, 4 cultural words (4,60%) byfunctionalequivalent, 2 cultural words (2,30%) by literal translation, 2 cultural words(2,30%) by naturalization, and 2 cultural words (2,30%) by omission.